Preventing pressure ulcers in aged care by auditing, and changing, work practices - Sharp, Catherine; Julie Campbell, (Asian Journal of Medical Sciences, 2022)
Background: Two nurse consultants concerned with ongoing pressure ulcer development in a 44-bed residential aged care facility in Sydney, Australia, audited pressure ulcers and the use of air mattresses. Aims and Objectives: To measure and reduce the prevalence of pressure ulcers; audit air mattresses in use; reduce the physical workload for care staff repositioning residents; introduce an alternating pressure air mattress, allow residents to sleep undisturbed, and provide bedside education for all nursing staff. Materials and Methods: Pressure ulcer prevalence was determined, “air” mattresses were inspected, and repositioning regimes were considered. All residents at risk of pressure ulcers were provided with a “Nodec A” mattress, allowed to sleep undisturbed, and bedside training was given to staff. Results: Pressure ulcer prevalence was 18.1%. Eight of 44 residents had a total of 10 pressure ulcers; four sacral, three heel ulcers, two buttocks, and one hip. An audit of “air” mattresses showed half, seven of 14 (50%), was not working. Four alarm lights were on; two were set on static mode and one was deflated. Six months after the introduction of the “Nodec A” alternating pressure air mattress all pressure ulcers had healed, and the facility was pressure ulcer free. Conclusion: Residents nursed on the “Nodec A” were pressure ulcer free and slept for hours without being repositioned and woken.